Organic Connective Social Movement Activism: A New Form of Citizenship Politics in Indonesia - Reja Fahlevi; Sunarso Sunarso; Suharno Suharno (University of Muhammadiyah Malang, 2026)
The emergence of organic social movements in Indonesia during the digital age reflects a shift in patterns of political activism toward more decentralized and network-based forms. This study aims to analyze the characteristics of connective activism within organic social movements and its implications for models of digital citizenship. The research employs a qualitative approach using a case study design, involving the observation of social media activities and a review of literature related to digital social movements. Data analysis was conducted using a descriptive-qualitative approach with a thematic framework to identify patterns of citizen participation and mobilization. The findings reveal that connective activism in Indonesia exhibits organic characteristics rooted in collectivity, social solidarity, and moral emotions, and is supported by the interaction between digital networks and local social structures. The case study of the “Panggilan Darurat” movement demonstrates that social media expands citizen participation and creates alternative spaces for public policy criticism. These findings underscore the emergence of a more inclusive, flexible, and connectivity-based model of digital citizenship.